Cyberspace computing (elements, components & applications) [ - Race, Antonia (New York : The English Press, 2014)
This handbook reviews elements, components & applications of Cyberspace Computing
1. Introduction to cyberspace -- 2. Cyberethics -- 3. Web search engine -- 4. Web page -- 5. Domain name -- 6. Cloud computing -- 7. Website -- 8. Cyberculture
Keywords: Cyberspace; Web services